Yu-Gi-Oh! GX. Vol. 8, Masked Hero vs. Vision Hero!! - Kageyama, Naoyuki (Shonen Jump manga., 2012)
"The next series of duels at Duel Academy are about to begin and Reggie Mackenzie's father, possessed by an evil spirit determined to wreak havoc, makes his move. By manipulating members of the group of visiting duelists from America, Mackenzie plants the seeds of destruction on Duel Academy Island. When Jaden takes on his next opponent, will he realize the evil he faces, or will an ancient spirit's scheme to resurrect itself go forward?"--P. [4] of cover.